Tailoring graphite fiber addition to improve high-temperature wear resistance graphite fiber/ Fe composite - Boer Cao; Qinyuan Huang; Yuhao Wu; Hongli Cao; Shangyang Zou; Quan Shan (Results in Engineering)
High-chromium iron-based high-temperature alloys are widely used in high-temperature wear environments. However, simple compositional adjustments are insufficient to enhance the wear resistance of metal parts at high temperatures. This study explores incorporating lightweight, lubricated, high-temperature-resistant graphite fibers (Gf) into ferrous metals to improve mechanical properties and wear resistance. Iron-based composites were prepared with varying graphite fiber contents (0, 5 vol%, 10 vol%, 15 vol%, and 20 vol%) using powder metallurgy. The study analyzed the effects of different Gf levels on the microstructure and hardness of the iron matrix. Oxidation tests defined the temperature range for wear tests, revealing that the Gf/Fe composites possess a wear temperature range from room temperature to 900 °C. Within this range, composites with 15 vol% Gf demonstrated a stable friction coefficient, lower wear volume, and lower wear rate, indicating superior wear resistance. The addition of Gf facilitated the bonding of carbon atoms with alloying elements like Cr, leading to carbide precipitation and a second-phase strengthening effect. Furthermore, Gf imparted excellent self-lubricating properties and high-temperature stability, enabling the composite to resist high-temperature wear failure effectively.